Characterisation of 15 novel microsatellite loci for the grey reef shark (Carcharhinus amblyrhynchos) - Momigliano, P.; Robbins, William; Gardner, M.; Stow, A. (Springer, 2014)
Grey reef sharks (Carcharhinus amblyrhynchos) are important apex predators on coral reefs, and their numbers have declined dramatically as a result of overfishing. Knowledge of environmental factors that shape gene flow is essential for developing appropriate management strategies, but the lack of suitable genetic markers has hindered research on this species. Here, we characterised 15 polymorphic microsatellite loci for grey reef sharks. None of the loci deviated significantly from Hardy-Weinberg equilibrium and there was no evidence of Linkage Disequilibrium. Several loci cross-amplified in other carcharhinid species, and will be useful in future studies of this family. © 2014 Springer Science+Business Media Dordrecht.